Identification of Germline Genetic Variants that Increase Prostate Cancer Risk and Influence Development of Aggressive Disease - Saunders, Edward J. (Cancers (Basel), 2021)
SIMPLE SUMMARY: The potential importance of germline genetic variation for identifying men at increased risk of prostate cancer has become increasingly recognised in recent years. We present an extensive review of the major developments in the identification of genetic loci, genes and individual variants associated with greater risk of prostate cancer, and what is currently known regarding whether these heritable prostate cancer risk factors can also inform likelihood of experiencing clinically significant rather than indolent forms of the disease. We finally discuss how these research discoveries might serve to inform clinical germline genetic testing guidelines and treatment options for prostate cancer in the future. ABSTRACT: Prostate cancer (PrCa) is a heterogeneous disease, which presents in individual patients across a diverse phenotypic spectrum ranging from indolent to fatal forms. No robust biomarkers are currently available to enable routine screening for PrCa or to distinguish clinically significant forms, therefore late stage identification of advanced disease and overdiagnosis plus overtreatment of insignificant disease both remain areas of concern in healthcare provision. PrCa has a substantial heritable component, and technological advances since the completion of the Human Genome Project have facilitated improved identification of inherited genetic factors influencing susceptibility to development of the disease within families and populations. These genetic markers hold promise to enable improved understanding of the biological mechanisms underpinning PrCa development, facilitate genetically informed PrCa screening programmes and guide appropriate treatment provision. However, insight remains largely lacking regarding many aspects of their manifestation; especially in relation to genes associated with aggressive phenotypes, risk factors in non-European populations and appropriate approaches to enable accurate stratification of higher and lower risk individuals. This review discusses the methodology used in the elucidation of genetic loci, genes and individual causal variants responsible for modulating PrCa susceptibility; the current state of understanding of the allelic spectrum contributing to PrCa risk; and prospective future translational applications of these discoveries in the developing eras of genomics and personalised medicine.